(3GdGbJUGO GdfbOj hGdeUQajs - (3HSGe(B, (3GdMLGQs ((3HjQhJ(B:s (3OGQ Gdefgd ddfTQ hGdJhRjY(B,s, 2006)
(3GdJHGOd hGdfbhO,CfhGY GdfbhO,GdfXe GdfbOjI,YQV GdfbhO,GdWdH Ydi GdfbhO,GdfehPL(BIS-LM(3,bjeI GdfbhO,Hfhc GdhOGFY hJWhQgG,ehGQO hGSJNOGeGJ GdHfhc GdJLGQjI,GdfXGe GdeUQaj GddHfGfj,fTCI hJWhQ GdHfhc GdeQcRjI,GdfXQjI GdfbOjI GdJbdjOjI,GdfXQjI GdfbOjI GdMOjKI,GdJVNe,GdONd Gdbhejs
(3HHdjhZQGajG(B:(3U(B.313-315 (3bGehS(B:(3U(B.316-319s